LOBULAR PLEOMORPHIC CARCINOMA VERSUS INVASING LOBULAR CARCINOMA: CLINICOPATHOLOGICAL CHARACTERISTICS AND PROGNOSTIC EVALUATION - Rabinovich, Iris; Jubainski, Eliza Maiara; Ghanem, Chaimaa; Costa, Natalia de Souza (Mastology, 2020)
Introduction: Pleomorphic lobular carcinoma (PLC) is a rare variant of invasive lobular carcinoma (ILC) that has a higher degree of cell atypia and pleomorphism, and has been associated with factors with a worse prognosis such as larger tumor size, and greater lymph node involvement, however, its real prognostic value is still not well defined. Objectives: To evaluate the clinical-pathological characteristics, overall survival, and disease-free survival in PLC and compare it to ILC. Method: All ILC and PLC cases submitted to surgery at Hospital Nossa Senhora das Graças from January 1st, 2008 to January 31st, 2018 were analyzed. The main clinical and pathological variables related to prognosis were analyzed, as well as the overall survival and disease-free survival for both groups. Results and Discussion: 77 cases of ILC and 35 of PLC were found. The PLC group presented factors of worse prognosis in relation to the ILC group, such as a higher histological grade (p<0.001), presence of lymphovascular invasion (p<0.001), greater axillary lymph node involvement (p=0.003), and higher Ki-67 rates (p<0.001). Contrary to what was expected, we did not find a greater expression of HER2 (p=0.095) in the PLC, and there was also no significant difference between the groups regarding disease-free survival and overall survival. Conclusions: PLC still cannot be considered as an independent variable with a worse prognosis and more studies are needed to better understand this entity.